Advances in Soft Computing and Its Applications 12th Mexican International Conference, MICAI 2013, Mexico City, Mexico, November 24-30, 2013, Proceedings, Part II - Castro, Félix; Gelbukh, Alexander; González, Miguel (Lecture Notes in Artificial Intelligence,, 2013)
The two-volume set LNAI 8265 and LNAI 8266 constitutes the proceedings of the 12th Mexican International Conference on Artificial Intelligence, MICAI 2013, held in Mexico City, Mexico, in November 2013. The total of 85 papers presented in these proceedings were carefully reviewed and selected from 284 submissions. The first volume deals with advances in artificial intelligence and its applications and is structured in the following five sections: logic and reasoning; knowledge-based systems and multi-agent systems; natural language processing; machine translation and bioinformatics and medical applications. The second volume deals with advances in soft computing and its applications and is structured in the following eight sections: evolutionary and nature-inspired metaheuristic algorithms; neural networks and hybrid intelligent systems; fuzzy systems; machine learning and pattern recognition; data mining; computer vision and image processing; robotics, planning and scheduling and emotion detection, sentiment analysis and opinion mining.